P54 Parental rating of follow-up care for their children in a european cohort of very preterm births. (3rd September 2019) - Seppanen, AV; Draper, E; El Rafei, R; Toome, L; Cuttini, M; Petrou, S; Barros, H; Zeitlin, J; ,
Abstract : Background: Infants born very preterm are at risk of developing multiple health and developmental problems. Because the prognosis of each individual child is unknown at discharge, follow-up is essential for identifying health needs early, enabling timely intervention and coordinating health services from multiple providers. Despite its recognized importance, there have been few evaluations of follow-up - in particular among parents, whose involvement is crucial for successful follow-up. This study investigated how parents rate their very preterm children's follow-up care in Europe. Methods: The data come from the Screening to improve Health In very Preterm infantS (SHIPS) study. It followed up the area-based EPICE cohort, which included all births before 32 weeks' gestation from all maternity units in 19 regions from 11 European countries in 2011/12. Perinatal data were abstracted from medical records and socioeconomic and child health data were collected with parent-report questionnaires at 2 and 5 years. At 5 years, parents rated the follow-up care received for their child's prematurity (poor, fair, good, excellent) and provided suggestions for improvement as free-text comments. We assessed poor and fair ratings and associated factors, including country, sociodemographic characteristics, perinatal characteristics and current health and developmental problems in STATA 14.0 using χ 2 ; tests and logistic regression models. We grouped free-text comments by themes and described them by country. Results: Questionnaires were filled in for 3414 children (51% response rate), by mothers (84%), fathers (14%) and other caretakers. 93% reported receiving follow-up care. Few (13.7%) judged follow-up care to be poor or fair, but this varied from <10% in France and the Netherlands to >20% in Denmark and Poland (p<0.001). Higher maternal education was related with more dissatisfaction (p<0.01). Poor/fair ratings were highest when children had diagnosed health problems, especially cerebral palsy (32.2%), and developmental delay (28.5%). After adjustment for diagnoses, perinatal characteristics were not significantly related to care ratings. Common themes from free-text comments (1032 responses) included the need for longer-term follow-up, focusing on more than physical health and lack of knowledge about prematurity among general practitioners. Some themes were mentioned more frequently in some countries such as waiting times (Poland), lack of coordination (Sweden) and length of maternity leave (Portugal). Conclusion: Dissatisfaction with follow-up care was low overall, but it was higher among those most reliant on health services. Many common themes emerged from parent comments despite geographic heterogeneity. Further research is needed to understand differences in reported satisfaction between countries and by maternal educational level.